1989
DOI: 10.1111/j.2042-7158.1989.tb06371.x
|View full text |Cite
|
Sign up to set email alerts
|

Vascular effects of propofol: smooth muscle relaxation in isolated veins and arteries

Abstract: Isolated hepatic portal veins and aorta taken from the rat were used to investigate the direct action of the intravenous anaesthetic propofol. This compound is known to produce a fall in blood pressure in man and animals and it has been suggested that the hypotension may result from a direct vasodilator action on the veins and arterioles. In our experiments propofol caused a dose related decrease of potassium-induced tone in both types of blood vessel. However, the concentrations required to produce this effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(36 citation statements)
references
References 7 publications
2
34
0
Order By: Relevance
“…One mechanism for the changes in SVR and venous capacitance may be a local eect on the blood vessel wall (Nakamura et al, 1992). Thus, propofol has been shown to alter the availability of free cytosolic calcium in vascular smooth muscle (Bentley et al, 1989;Bunting et al, 1989;Chang & Davis, 1993;Introna et al, 1993;Yamanoue et al, 1994;Kamitani et al, 1995;Wallerstedt & Bodelsson, 1997a) and also to aect the function of the endothelium (Park et al, 1992;Petros et al, 1993;Mimaroglu et al, 1994;Gacar et al, 1995;Park et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…One mechanism for the changes in SVR and venous capacitance may be a local eect on the blood vessel wall (Nakamura et al, 1992). Thus, propofol has been shown to alter the availability of free cytosolic calcium in vascular smooth muscle (Bentley et al, 1989;Bunting et al, 1989;Chang & Davis, 1993;Introna et al, 1993;Yamanoue et al, 1994;Kamitani et al, 1995;Wallerstedt & Bodelsson, 1997a) and also to aect the function of the endothelium (Park et al, 1992;Petros et al, 1993;Mimaroglu et al, 1994;Gacar et al, 1995;Park et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Several animal studies have reported that propofol reduces the preload by a direct effect on venous smooth muscle tone [8,27]. In contrast, it has been reported that the mechanism of peripheral vasodilatation [28] and venodilatation [29] primarily involves the inhibition of sympathetic vasoconstrictor nerve activity.…”
Section: Discussionmentioning
confidence: 96%
“…Richmond Agitation and Sedation Scale Scores After IV Injection of PHAX and Propofol www.anesthesia-analgesia.org aNesthesia & aNalgesia the brainstem. 40 A potential explanation for the difference in blood pressure is that propofol increases capacitance and decreases venous return by a direct action on the smooth muscle of veins 41,42 and alphaxalone does not. These differences in side effects warrant further study.…”
Section: Discussionmentioning
confidence: 99%